ANALISIS HUBUNGAN KEPEMIMPINAN EFEKTIF DAN KOMUNIKASI KEPEMIMPINAN DENGAN KEPUASAN PERAWAT DI RUANG RAWAT INAP RS - Yeni Nur Rahmayanti; Christiana Arin Proborini; Nuriyah Yuliana (Jurnal Infokes, 2020)
The satisfaction of nurses at Karanganyar Hospital is less than optimal (70.37%) This is due to lack of attention and giving head of space. Nurse satisfaction is an emotional feeling that a nurse feels after action. The satisfaction of this nurse is strongly influenced by how leadership of the head only and communication in conveying the subordinate policy. Effective leadership is used by the head of space to lead his subordinates. The communication that occurred in between the leadership and the subordinate was a fundamental mechanism in demonstrating disappointment or their satisfaction. This type of quantitative study, is descriptive correlational correlative and this research uses the Cross Sectional approach. The number of samples was 61 respondents taken using the Purposive Sampling technique. The results of the analysis showed the presence of effective leadership relationship and effective communication with the satisfaction of nurses with a significance value of 0.000 < 0.05. Based on the research, it is recommended the need for education, training and effective leadership implementation to all nursing managers to create effective leadership and communication to improve nurse satisfaction.